THE PERCEPTION OF THE THIRD YEAR RAMBAH SAMO JUNIOR HIGH SCHOOL STUDENTS TOWARD WHATSAPP FOR ENGLISH LEARNING MEDIUM - Annisa Arum Melati; M. Syarfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The objective of this research is to find out the perception of the third yearRambah Samo junior high school students toward Whatsapp for English learningmedium. This research uses quantitative method with a survey approach. The sample forthis research included 42 third year SMPN 5, Rambah Samo who experienced in learningEnglish through WhatsApp as learning medium. The instrument of this research was aquestionnaire using a Likert-type scale. Based on the recapitulation of perceptionindicators, it is known that the third year students of SMPN 5 Rambah Samo goodtowards this learning medium. The score obtained is 74.4. They admit that WhatsApp isan interesting learning medium. This can increase their self-confidence, create creativityin thinking, encourage them participate well and bravely in group discussions. On top ofthat, using WhatsApp they can understand the material better. And they admit that, using WhatsApp as a learning medium is time and cost efficiency.Key Words: Perception, WhatsApp, Learning Medium.